Redesain Produk Berfokus Pada Customer Requirements Dengan Integrasi Axiomatic Design dan House of Quality - Debrina Puspita Andriani; Mochamad Choiri; FX. Berry Desrianto (Jurnal Ilmiah Teknik Industri, 2018)
Problems related to the storage of shoes include discomfort in putting shoes and shoes are still dusty. Shape shelves are generally open. Shoe rack products need to be developed using integration of axiomatic design method with house of quality or called axiomatic house of quality (AHOQ). AHOQ is a modification of HOQ that aims to reduce errors arising from the translation of user statements that are not appropriate in the needs of the product. With the customer requirements are clear, then can determine the functional requirements and design parameters are more appropriate. This research produces dimension specification of shoe rack according to anthropometry data of Indonesia and for material used. Shoe rack is also designed to have a door made of acrylic tansparan, so in addition to protect shoes from dust, facilitate in finding and finding shoes to be used. Testing using ANSYS software, obtained the ability to receive maximum pressure and product safety factors.